Ataxia Telangiectasia Mutated Dysregulation Results in Diabetic Retinopathy. (17th November 2015) - Bhatwadekar, Ashay D.; Duan, Yaqian; Chakravarthy, Harshini; Korah, Maria; Caballero, Sergio; Busik, Julia V.; Grant, Maria B.
Abstract: Ataxia telangiectasia mutated (ATM) acts as a defense against a variety of bone marrow (BM) stressors. We hypothesized that ATM loss in BM-hematopoietic stem cells (HSCs) would be detrimental to both HSC function and microvascular repair while sustained ATM would be beneficial in disease models of diabetes. Chronic diabetes represents a condition associated with HSC depletion and inadequate vascular repair. Gender mismatched chimeras of ATM −/− on wild type background were generated and a cohort were made diabetic using streptozotocin (STZ). HSCs from the STZ-ATM −/− chimeras showed (a) reduced self-renewal; (b) decreased long-term repopulation; (c) depletion from the primitive endosteal niche; (d) myeloid bias; and (e) accelerated diabetic retinopathy (DR). To further test the significance of ATM in hematopoiesis and diabetes, we performed microarrays on circulating angiogenic cells, CD34 + cells, obtained from a unique cohort of human subjects with long-standing (>40 years duration) poorly controlled diabetes that were free of DR. Pathway analysis of microarrays in these individuals revealed DNA repair and cell-cycle regulation as the top networks with marked upregulation of ATM mRNA compared with CD34 + cells from diabetics with DR. In conclusion, our study highlights using rodent models and human subjects, the critical role of ATM in microvascular repair in DR.